2020
DOI: 10.1177/000313482008600340
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Research Productivity of Trauma Surgeons

Abstract: This study aimed to identify factors that promote and impede research participation and productivity by Eastern Association for the Surgery of Trauma (EAST) surgeons. In addition, the study aimed to determine what changes can be implemented by surgical departments to improve this research productivity and granting. A 25-question anonymous research survey tool was offered to EAST surgeons. The questions analyzed factors including demographics, career accomplishments, current institution type, educational/resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…16 Protected research time, mentorship, statistical and financial support, laboratory space, practicing for a university-affiliated hospital, and nonclinical research staff have also shown to be significantly associated with increased research productivity of general, burn, and plastic surgeons. 11,17 In our study, we compared productivity among TOPS in order to elucidate factors that contribute to research productivity. If resources and resource allocation are the main contributors in effect, no significant difference in publication number between TOPS might be expected.…”
Section: Discussionmentioning
confidence: 99%
“…16 Protected research time, mentorship, statistical and financial support, laboratory space, practicing for a university-affiliated hospital, and nonclinical research staff have also shown to be significantly associated with increased research productivity of general, burn, and plastic surgeons. 11,17 In our study, we compared productivity among TOPS in order to elucidate factors that contribute to research productivity. If resources and resource allocation are the main contributors in effect, no significant difference in publication number between TOPS might be expected.…”
Section: Discussionmentioning
confidence: 99%
“…The scanning portion of a pediatric echocardiogram is the most time-consuming task and removing this role from the physician allows for more focus elsewhere. Knowing that physician research productivity increases with dedicated research time ( 26 ), the sonographer’s activity has an indirect impact on the team’s or unit’s research productivity.…”
Section: Sonographer’s Impactsmentioning
confidence: 99%